Greek Laughter: A Study of Cultural Psychology from Homer to Early Christianity - Halliwell, Stephen (Cambridge University Press, 2013)
This is the first book to offer an integrated reading of ancient Greek attitudes to laughter. Taking material from literature, myth, philosophy, religion and social mores, it analyses both the theory and the practice of laughter as a richly revealing expression ofGreek values and mentalities. From the exuberantly laughing gods of Homeric epic to the condemnation of laughter by some early Church fathers, the subject provides a fascinating means of investigating complex features of cultural psychology. Greek society developed distinctive institutions (including the symposium and certain religious festivals) for the celebration of laughter as a capacity which could bridge the gap between humans and gods; but it also feared laughter for its power to expose individuals and groups to shame and even violence. Caught between ideas of pleasure and pain, friendship and enmity, play and seriousness, laughter became a theme of recurrent interest in various contexts. Employing a sophisticated model of cultural history, Stephen Halliwell traces elaborations of the theme in a series of important poetic and prose texts: ranging far beyond certain modern accounts of ‘humour’, he shows how perceptions of laughter helped to shape Greek conceptions of the body, the mind and the meaning of life.